Terpenes in the Aroma of Grapes and Wines: A Review - Marais, J. (South African Journal of Enology and Viticulture, 2017)
This paper reviews some aspects of terpenes and terpene derivatives in grapes and wines, such as the identification of these compounds, their use in the identification of and differentiation between cultivars, the effect of grape maturity and wine-making techniques on terpene concentrations and wine quality, as well as transformations of terpenes in grapes and wine.